Long‐Term Habitat Use Patterns of Ray Assemblages in Coastal and Inshore Waters of the Eastern Gulf of Mexico - Julian R. Gatch; Matthew E. Kimball; Robert P. Dunn; Alan Moore; Lina Vanesa Garzón‐Peña; Angelica Barrera‐García (Marine Ecology, 2026)
Rays are common marine mesopredators that use coastal and estuarine habitats during multiple life history stages for critical functions. They are long‐lived, late to mature, and have low reproductive output, making them vulnerable to and slow to recover from population threats such as overfishing and habitat loss. Considering this, examining ray abundance, assemblage structure and distribution, as well as identifying ray habitat use patterns, especially over long time periods, is important. Fishery‐independent sampling (tangle nets, bottom longlines, and rod and reel) was used to examine ray species composition, distribution, and abundance in St. Joseph Sound over a 10‐year period. Six different ray species were caught, with three species making up 93.5% of the catch: southern stingray ( Hypanus americanus ), cownose ray ( Rhinoptera sp.), and bluntnose stingray ( Hypanus say ). Ray abundance and assemblage composition varied across the study area, potentially due to differences in abiotic or biotic conditions. Analyses revealed that this area is used by multiple ray species for multiple life history functions, including use by cownose rays as a pupping area. This study represents the first in‐depth analysis of the batoid community in St. Joseph Sound, and collectively, the results suggest that the study area serves as important habitat supporting ray communities in the coastal and inshore waters of the eastern Gulf of Mexico.